(untitled) (Archives of Criminology, 2023)
Yugoslavia’s disintegration in the 1990s resulted in the differentiation of five different countries, meaning the building of five different criminal legal systems with many similarities at that time, but also with differences in the years to come. The Republic of North Macedonia brought its first Criminal Code in 1996, decriminalising some of the previous crimes connected to socialist system norms, and criminalising activities characteristic of capitalist social systems. From its basic draft, the Criminal Code had been changed twenty-eight times by 2018 in accordance with crime changes and flows, and societal changes. Using crime statistics published by the Republic of North Macedonia’s State Statistical Office in an annual publication, ‘Perpetrators of Crimes’, this paper’s goal will be to present the trends in crime volume and dynamics, the changes in the breakdown of crimes as result of decriminalisation and criminalisation, and the possible future challenges and changes, as well as the trends and changes to the state’s criminal policy, the frequent use of imprisonment as a sanction, and the very rare use of alternative measures apart from probation. The authors will use the comparative method, basic statistics, and content analysis in the general overview of crime volume and dynamics, crime structure, and structural changes. Such an analysis can help in tackling the most important chronological points during the period in question and connect them with political, social, security, and economic challenges for the country.